Simplifying
6k + -9 = -15
Reorder the terms:
-9 + 6k = -15
Solving
-9 + 6k = -15
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '9' to each side of the equation.
-9 + 9 + 6k = -15 + 9
Combine like terms: -9 + 9 = 0
0 + 6k = -15 + 9
6k = -15 + 9
Combine like terms: -15 + 9 = -6
6k = -6
Divide each side by '6'.
k = -1
A because my test said so
Answer:
Yes they equal eachother beacuse the math teacher told me that they do
Step-by-step explanation:
so first you see pattern look up lok down then answer the question
The answer should be the first one, SF = 1/2
Answer:
The domain of the inverse of a relation is the same as the range of the original relation. In other words, the y-values of the relation are the x-values of the inverse.
Thus, domain of f(x): x∈R = range of f¯¹(x)
and range of f(x): x∈R =domain of f¯¹(x)